(untitled) (Comprehensive Journal of Science, 2025)
This research aims to evaluate the impact of applying sustainable construction management principles on operational efficiency, cost, and project duration in Libya, with a particular focus on environmental dimensions as a key factor in improving the overall performance of the construction sector. A field research was conducted on three real projects located in the cities of Zliten, Misrata, and Tripoli, using questionnaires and structured interviews with 60 engineers and supervisors. The research employed a descriptive-analytical approach supported by statistical analysis. The findings revealed that projects implementing sustainable management principles recorded a 24% improvement in operational efficiency, a 21% reduction in costs, and a 15% decrease in project duration compared to conventional projects. The results also indicated that the awareness level regarding the importance of sustainable management reached 78% among participants, despite the absence of institutional regulatory frameworks supporting its formal adoption. The research concludes that applying sustainable management practices in Libyan projects is a national necessity to achieve a balance between economic feasibility and environmental protection. It recommends establishing a National Authority for Sustainable Construction and integrating Artificial Intelligence (AI) and Building Information Modeling (BIM) tools into planning and implementation to enhance the environmental and technical performance of projects.